Critical traumatic brain injury is associated with worse coagulopathy. Issue 2 (August 2021) - Cucher, Daniel; Harmon, Laura; Myer, Brian; Ngyuen, Andrew; Rankin, Timothy; Cook, Alan; Hu, Charles; Tesoriero, Ronald; Scalea, Thomas; Stein, Deborah
Abstract : Objectives: As thromboelastography (TEG) becomes the standard of care in patients with hemorrhagic shock (HS), an association between concomitant traumatic brain injury (TBI) and coagulopathy by TEG parameters is not well understood and is thus investigated. Methods: Retrospective analysis of trauma registry data at a single level 1 trauma center of 772 patients admitted with head Abbreviated Injury Scale (AIS) score of 3 and TEG studies between 2014 and 2017. Patients were stratified to moderate-severe TBI by head AIS scores of 3 and 4 (435 patients) and critical TBI by head AIS score of 5 (328 patients). Hemorrhagic shock was defined by base deficit of 4 or shock index of 0.9. Statistical analysis with unpaired t tests compared patients with critical TBI with patients with moderate-severe TBI, and patients were grouped by presence or absence of HS. A comparison of TBI data with conventional coagulation studies was also evaluated. Results: In the setting of HS, critical TBI versus moderate-severe TBI was associated with longer R time ( p = 0.004), longer K time ( p < 0.05), less acute angle ( p = 0.001), and lower clot strength and stability (maximum amplitude [MA]) ( p = 0.01). Worse TBI did not correlate with increased fibrinolysis by clot lysis measured by the percentage decrease in amplitude at 30 minutes after MA ( p = 0.3). Prothrombin time and international normalized ratio failed to demonstrate more severe coagulopathy, while partial thromboplastin time was found to correlate with severity of TBI ( p = 0.01). In patients with critical TBI, the presence of HS correlated with a statistically significant worsening of all parameters ( p < 0.05) except for clot lysis measured by the percentage decrease in amplitude at 30 minutes after MA (LY-30). Conclusion: Thromboelastography demonstrates that, with and without hemorrhagic shock, critical TBI correlates with a significant worsening of traumatic coagulopathy in comparison with moderate/severe TBI. In HS, critical TBI correlates with impaired clot initiation, impaired clot kinetics, and impaired platelet-associated clot strength and stability versus parameters found in moderate-severe TBI. Hemorrhagic shock correlates with worse traumatic coagulopathy in all evaluated patient groups with TBI. Conventional coagulation studies underestimate TBI-associated coagulopathy. Traumatic brain injury–associated coagulopathy is not associated with fibrinolysis. LEVEL OF EVIDENCE: Prognostic/epidemiological, level IV; prognostic/epidemiological, level III.